Minimum Ledge Tie Reinforcement for UHPFRC Ledge Beams - Ahmed M. Yousef; Mohamed E. El Madawy; Karim Abd El-Hady (International Journal of Concrete Structures and Materials)
Abstract Ledge beams are employed as the primary girders in numerous existing bridges, parking garages and high-rise buildings. No experimental investigations have been reported on Ultra-High Performance Fiber Reinforced Concrete (UHPFRC) ledge beams yet. This paper presents an experimental and numerical program to investigate UHPFRC ledge beams with various ratios of ledge tie reinforcement. The experimental program included eight full-scale ledge beams constructed from UHPFRC with concrete cube compressive strength of 146.1 MPa. The results revealed that failure modes of tested specimens depend mainly on ledge tie reinforcement. Increasing the ledge tie reinforcement ratio in specimens led to a significant enhancement of the ultimate strength and overall stiffness. The presence of ledge ties at the minimum ratio specified by the codes contributed to an approximate 65.0% increase in the ultimate load. The estimated failure modes for specimens using (AASHTO–LRFD 2020) and Strut-and-Tie Model (STM) according to (ACI 318-2019) were identical with experiments, while the predictions of (PCI 2020) were not identical with 50.0% of the experimental results. The predictions of ultimate strength of specimens based on the equations of (PCI 2020) and STM according to (ACI 318-2019) were conservative. A three-dimensional numerical model was proposed to predict the complete response of the tested UHPFRC ledge beams.